Extended-spectrum β-lactamase-producing Escherichia coli isolated from captive primates: characteristics and horizontal gene transfer ability analysis - Wenhao Zhong; Yuxin Zhou; Mengjie Che; Liqin Wang; Xingyu Tian; Chengdong Wang; Yuehong Cheng; Haifeng Liu; Ziyao Zhou; Guangneng Peng; Kun Zhang; Yan Luo; et al. (PLoS ONE, 2025)
The rapid spread of extended-spectrum β-lactamases (ESBLs)-producing Escherichia coli (ESBL-EC) around the world has become a significant challenge for humans and animals. In this study, we aimed to examine the characteristics and horizontal gene transfer (HGT) capacity of ESBL-EC derived from captive primates. We screened for ESBL-EC among a total of 444 multidrug-resistant (MDR) E. coli strains isolated from 13 zoos in China using double-disk test. ESBL genes, mobile genetic elements (MGEs), and virulence-associated genes (VAGs) in ESBL-EC were detected through polymerase chain reaction (PCR). Furthermore, conjugation experiments were conducted to examine the HGT capacity of ESBL-EC, and the population structure (phylogenetic groups and MLST) was determined. Our results showed that a total of 69 (15.54%, 69/444) ESBL-EC strains were identified, and 5 variants of blaCTX and 3 variants of blaTEM were detected. The highest detection rate was blaCTX-M-55 (49.28%, 34/69), followed by blaCTX-M-15 (39.13%, 27/69). Ten MGEs were detected and the most prevalent was IS26 (78.26%, 54/69), followed by ISEcp1 (60.87%, 42/69). Eighteen combinations of MGEs were detected, in which ISEcp1 + IS26 was predominant (18.84%, n = 13). A total of 15 VAGs were detected and the most prevalent was fimC (84.06%, 58/69), followed by sitA (78.26%, 54/69). Furthermore, HGT ability analysis results showed that 40.58% (28/69) of ESBL-EC strains exhibited the ability to engage in conjugative transfer. Plasmid typing revealed that IncFIB (78.57%, 22/28) had the highest detection rates. Furthermore, antibiotic resistance genes (ARGs) of blaTEM-135, tetA and qnrS; MGEs of IS26, trbC and ISCR3/14 showed high rates of conjugative transfer. The population structure analysis showed that the phylogroup B1 and ST2161 were the most prevalent. ESBL-EC poses a potential threat to captive primates and may spread to other animals, humans, and the environment. It is imperative to implement measures to prevent the transmission of ESBL-EC among captive primates.